2024
DOI: 10.1001/jamainternmed.2024.0037
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Rapid Respiratory Virus Testing in Emergency Departments

Tilmann Schober,
Kimberly Wong,
Gaëlle DeLisle
et al.

Abstract: ImportanceRapid tests for respiratory viruses, including multiplex panels, are increasingly available in emergency departments (EDs). Their association with patient outcomes remains unclear.ObjectiveTo determine if ED rapid respiratory virus testing in patients with suspected acute respiratory infection (ARI) was associated with decreased antibiotic use, ancillary tests, ED length of stay, and ED return visits and hospitalization and increased influenza antiviral treatment.Data SourcesOvid MEDLINE, Embase (Ovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…To the Editor We read with great interest the study conducted by Schober et al, in which the objective was to assess whether rapid respiratory virus testing in emergency department patients suspected of having acute respiratory infections correlates with reduced antibiotic administration, fewer ancillary tests, shorter emergency department duration, and lower rates of emergency department revisits and hospital admissions, alongside an increase in influenza antiviral therapy. I would like to start by commending the author for adhering to the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) reporting guideline and registering the protocol in the International Prospective Register of Systematic Reviews (PROSPERO), which established a strong foundation for this systematic review . However, when analyzing the research methods, I identified several areas that could further strengthen the study.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…To the Editor We read with great interest the study conducted by Schober et al, in which the objective was to assess whether rapid respiratory virus testing in emergency department patients suspected of having acute respiratory infections correlates with reduced antibiotic administration, fewer ancillary tests, shorter emergency department duration, and lower rates of emergency department revisits and hospital admissions, alongside an increase in influenza antiviral therapy. I would like to start by commending the author for adhering to the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) reporting guideline and registering the protocol in the International Prospective Register of Systematic Reviews (PROSPERO), which established a strong foundation for this systematic review . However, when analyzing the research methods, I identified several areas that could further strengthen the study.…”
mentioning
confidence: 99%
“…First, the initial study noted that selection was conducted by a single reviewer . Although this practice is not uncommon, engaging 2 independent reviewers from the outset could minimize selection bias, ensuring a more comprehensive and unbiased coverage of the relevant literature …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In Reply We express our gratitude to Acuña-Rocha for raising 4 important points regarding the methods of our systematic review and meta-analysis of randomized clinical trials on the impact of rapid respiratory virus testing in emergency departments on clinical outcomes …”
mentioning
confidence: 99%